The symbiotic binary ZZ CMi: Intranight variability and suggested outbursting nature. Issue 7 (23rd September 2021) - Zamanov, Radoslav K.; Stoyanov, Kiril A.; Kostov, Andon; Kurtenkov, Alexander; Nikolov, Grigor; Latev, Georgi; Bode, Michael F.; Martí, Josep; Luque‐Escamilla, Pedro L.; Tomov, Nikolay; Nikolov, Yanko M.; Boeva, Svetlana S.
Abstract: We present photometric and spectral observations of the symbiotic star ZZ CMi. We detect intranight variability—flickering and smooth variations in U band. The amplitude of the flickering is about 0.10 − 0.20 mag in U band. In the B band, the variability is lower, with amplitude ≤ 0.03 mag. We also detect variability in the H α and H β emission lines, and find an indication for outflow with velocity of about 120–150 km/s. The results indicate that ZZ CMi is an accretion‐powered symbiotic containing an M4‐M6 III cool component with a white dwarf resembling recurrent novae and jet‐ejecting symbiotic stars.